Análise do processo orçamentário de uma organização pública: um estudo no município de Gentil/RS - Tonini, Cristine (2023)
In this study on the budget process of the Municipal Government of Gentil/RS, the objective was to analyze the stages of the process and identify bottlenecks to improve the efficiency of the public budget. Data collection was done through group interviews and document analysis, using tools such as Flowchart, 5W1H, GUT Matrix and Ishikawa Diagram to interpret them. The results highlighted the importance of meeting legal deadlines and community participation, identifying challenges in areas such as expense control, inventory management, communication between technicians and managers, and compliance with the LRF. In-depth analysis led to the development of strategies to overcome these obstacles, focusing on transparency, effective communication and financial control. The search contributed to the understanding of the municipal budget process and offered crucial knowledge to improve local public administration in terms of effectiveness and responsibility.